Cyclists body stability during 30 seconds isokinetic sprint cycling exercise is related with FMS score, pedalling power symmetry and smoothness - Rannama, I.; Pedak, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Notable bilateral pedalling kinetics asymmetry is measured during steady state cycling and it has tendency to decrease due to higher power output or accumulated fatigue (Carpes et al., 2010). Less examined is pedalling kinetics asymmetry during maximal cycling and how it affects the performance. It is found that knee extensors and upper-body movement asymmetry affects negatively 5 sec. sprint cycling performance (Rannama et al., 2015), but there is no evidence how the core stability is related with this. The aim of the present study was to investigate how the body movement efficiency during 30 sec maximal cycling is related with pedalling technique, pedalling symmetry and core stability. Methods: The pedalling power (Pped) and smoothness (PS- mean and peak effective force ratio in %) of 37 competitive cyclists (18.8±2.8 y, 181.4±6.2 cm, 74.4±7.2 kg) were measured bilaterally with Garmin Vector pedals during 30s isokinetic (cadence fixed to 100 rpm) seated sprint cycling test. Absolute bilateral symmetry index (ASI %) between DO and ND side in Pped and PS were computed. The Cyclus 2 ergometer was mounted on Kistler force plates and cyclists body Centre of Gravity movement power (PCoG) were measured. The effectual power ratio coefficient (Pcof in %) between PCoG and Pped were computed. The state of cyclists Core stability evaluated with Functional Movement Screening test (FMS). The correlation analyse and a forward stepwise regression analyse between Pcof and Pped (w/kg), PS, Pped ASI, PS ASI and FMS score were made. Results: The average values of measured parameters: Pped 822 ± 106 W and 11.1±1.0 W/kg, PS 32.8±2.6%, Pped ASI 5.1±4.5 %, PS ASI 7.4±4.1%, PCoG 24.3±6.9 W, Pcof 2.9±0.7 %, FMS 14.6±2. There was no significant correlation between Pped and Pcof , PS, ASI and FMS, but higher Pped associated with higher PCoG (r=0.43). Between Pcof and other independent variables was developed regression model: Pcof=7.838-0.125xPS+0.062xPped ASI-0.076xFMS. Discussion: The results of present study indicate that sprint cycling performance is not linearly related with body movement efficiency, but the relative amount of power that are generated by extra movements are positively related with Ppow asymmetry and negatively with PS and Core stability (FMS). This supports partly our previous findings between 5 sec. sprint performance, knee extensors strength and upper body kinematics asymmetry (Rannama et al., 2015).